Caso de estudio: análisis y diagnóstico de una empresa del sector agroindustrial peruano, propuesta de un plan estratégico - Mallaupoma Riquelme, Luis Angel (2019)
The business administration is under the action of professionals, however, it is necessary to boost the company’s growth with the development of a strategic plan in which it will be necessary to give greater strength to the key areas and establish new strategies that allow the expansion of the brand as well as the increase in the preference for the final consumer resulting in the projection of higher sales and high profit margins for the company exceeding the profits obtained in 2016.